1997
DOI: 10.1002/pro.5560060420
|View full text |Cite
|
Sign up to set email alerts
|

Production, crystallization, and preliminary X‐ray analysis of rabbit skeletal muscle troponin complex consisting of troponin C and fragment (1‐47) of troponin I

Abstract: Abstract:Troponin is a ternary protein complex consisting of subunits TnC, TnI, and TnT, and plays a key role in calcium regulation of the skeletal and cardiac muscle contraction. In the present study, a partial complex (CI47) was prepared from Escherichia coli-expressed rabbit skeletal muscle TnC and fragment 1-47 of TnI, which is obtained by chemical cleavage of an E. coliexpressed mutant of rabbit skeletal muscle TnI. Within the ternary troponin complex, C147 is thought to form a core that is resistant to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…More attention has been given to the biologically important interaction between TnC and the N‐terminal region of TnI [Ngai and Hodges, 1992; Sheng et al, 1992; Farah et al, 1994; Krudy et al, 1994; Dong et al, 1997; Saijo et al, 1997; Tripet et al, 1997; Van Eyk et al, 1997; Filatov et al, 1998; Vassylyev et al, 1998a,b; Abbott et al, 2000; Mercier et al, 2000] since it was first identified by Syska et al [1976]. In our previous investigation, we have shown that synthetic peptides corresponding to the N‐terminus of TnI were able to interact with TnC and prevent TnC from neutralizing TnI or TnI inhibitory peptide (Ip) induced inhibition of acto‐S1‐TM ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…More attention has been given to the biologically important interaction between TnC and the N‐terminal region of TnI [Ngai and Hodges, 1992; Sheng et al, 1992; Farah et al, 1994; Krudy et al, 1994; Dong et al, 1997; Saijo et al, 1997; Tripet et al, 1997; Van Eyk et al, 1997; Filatov et al, 1998; Vassylyev et al, 1998a,b; Abbott et al, 2000; Mercier et al, 2000] since it was first identified by Syska et al [1976]. In our previous investigation, we have shown that synthetic peptides corresponding to the N‐terminus of TnI were able to interact with TnC and prevent TnC from neutralizing TnI or TnI inhibitory peptide (Ip) induced inhibition of acto‐S1‐TM ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Before the availability of crystal structures of actin and myosin subfragment 1, for example, distances derived from RET measurements were used to deduce the spatial arrangements of certain residues in these proteins (e.g., Botts et al, 1989;Kekic et al, 1996;Miki et al, 1992, and references therein;Park et al, 1991). Although a complex of an Nterminal fragment of TnI and TnC has recently been crystallized (Saijo et al, 1997), no crystal of Tn or of a complex containing intact TnI has been available for x-ray diffraction. We (Tao et al, 1989) and others (Wang and Cheung, 1986) have used RET to measure distances between various sites in these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative is expression in insect cells which can produce expression levels of 120-200 mg/L of infected cells using special enhancer sequences (16). E. coli cells are prokaryotic and thus generally do not acetylate the N-terminus of eukaryotic proteins although there are exceptions (17). Tm expressed in E. coli is not acetylated and will be largely inactive (14,18).…”
mentioning
confidence: 99%